2013
DOI: 10.1074/jbc.m112.394668
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variants of Photosystem II Subunit D1 Tune Photochemical Fitness to Solar Intensity *

Abstract: Background: Cyanobacteria use multiple PSII-D1 isoforms to adapt to environmental conditions. Results: D1:2 achieves higher quantum efficiency of water oxidation and biomass accumulation rate at high light versus D1:1; the latter is more efficient at low light due to less charge recombination. Conclusion: A functional advantage for D1:1 is revealed for the first time. Significance: Improved photochemical efficiency at low light suggests an evolutionary advantage to retain D1:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 69 publications
4
27
0
Order By: Relevance
“…Qian et al (2012) demonstrated that exposure to streptomycin in Chlorella vulgaris reduced the psbA transcript abundance. The D1 subunit of the photosystem II contains most of the amino acid residues that binds the core of the water-oxidizing complex (Vinyard et al, 2013). In this investigation we found that the reduction in the content of protein D1 due to exposure to streptomycin is directly related with the reduction on growth and also to the quantum yield of PSII, the electron transport and the photosynthetic oxygen evolution.…”
Section: Discussionmentioning
confidence: 89%
“…Qian et al (2012) demonstrated that exposure to streptomycin in Chlorella vulgaris reduced the psbA transcript abundance. The D1 subunit of the photosystem II contains most of the amino acid residues that binds the core of the water-oxidizing complex (Vinyard et al, 2013). In this investigation we found that the reduction in the content of protein D1 due to exposure to streptomycin is directly related with the reduction on growth and also to the quantum yield of PSII, the electron transport and the photosynthetic oxygen evolution.…”
Section: Discussionmentioning
confidence: 89%
“…While many of the alternate residues affect photoprotection and electron transfer [23], there are some substitutions in the region around the OEC that affect Y Z electron transfer and progression through the Kok cycle. The inclusion of the psbA2-encoded D1 protein of Thermosynechococcus elongatus hinders the S 2 -to-S 3 transition [24], due to changes in the hydrogen-bond network around D1-P173M [25 ].…”
Section: Y Z Electron Transfermentioning
confidence: 99%
“…The expression of these protein isoforms is controlled by differential transcriptional regulation of multiple psbA gene copies within a single genome (40,41). Subtle differences in the amino acid sequences of these D1 isoforms control the efficiency of PSII specifically at very high and very low light intensities (42)(43)(44)(45) or under low-oxygen conditions (46,47). By contrast, green algae and plants contain only a single D1 isoform (40) and consequently utilize a different regulation system for dealing with varying light intensities.…”
Section: The Reaction Centermentioning
confidence: 99%